ANALYSIS OF THE EFFECTIVENESS OF THE SIBANGMAN WEBSITE AS AN INFORMATION MEDIA FOR REPORTING STUNTING INFORMATION AT THE BAPPEDA OF JAMBI CITY - Rahma Dina Sari; Arnild Augina Mekarisce; Adila Solida; Rumita Ena Sari (PT. Radja Intercontinental Publishing, 2026)
This study was motivated by the importance of government websites as media for stunting information and reporting that support cross-sector coordination, data transparency, and the acceleration of stunting reduction programs. The study aimed to analyze the effectiveness of the SIBANGMAN Website as a stunting reporting information medium at the Regional Development Planning Agency of Jambi City based on the human, organization, technology, and fit aspects. This study employed a qualitative approach with a descriptive design. Informants were selected purposively and consisted of one key informant, three main informants, and six supporting informants from related regional agencies. Research instruments included interview guidelines, observation sheets, audio recorders, field notes, and documentation. Data were collected through in-depth interviews, observation, and documentation, while data analysis was conducted using data reduction, data display, and conclusion drawing supported by source triangulation. The findings showed that the SIBANGMAN Website was quite effective in supporting stunting reporting through an integrated system, good information quality, and strong organizational support, although challenges remained in digital literacy, automatic notification features, and system interface design. The study concludes that SIBANGMAN has fulfilled its informative and coordinating functions in stunting reporting, yet further technical development and user capacity strengthening are still required to optimize its sustainability and effectiveness.